Utilization of Environmentally Friendly Technology in Shallot Farming to Increase Farmer Production and Income after the Covid 19 Pandemic - Arman, Arman; Nuddin, Andi; Masnur, Masnur; Irmayani, Irmayani; Hasnia, Hasnia (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2023)
Shallots are one of the main commodities that have a hinge value, so that their cultivation is spread in almost all regions. Shallots are also multifunctional, used as a spice in the kitchen in life. In addition, onion bulbs can also be used as traditional medicine which our ancestors often used as a medicine for stomachaches and healing wounds or infections, medicine for stomach ulcers, diabetes and coughs. Shallots are a lucrative source of income but cultivation is difficult, especially to deal with pests and caterpillars. The aims of this study were: 1) to show the effect of applying mosquito net technology to increasing people's income in Anggeraja District, Enrekang Regency. 2) shows the effect of applying mosquito net technology to increasing farmers' income in Anggeraja District, Enrekang Regency. 3) demonstrating the application of proper mosquito net technology for economic feasibility tests in Anggeraja District, Enrekang Regency. This study uses descriptive qualitative research methods, because in its implementation it includes data and analysis, the data used are primary data and secondary data. The sample in this study was fifty people using excel and analysis using R/C ratio analysis. The results of this study indicate that the average income level of shallot farmers in Anggeraja District, Enrekang Regency is IDR 63,250,376.00/million ha, with an R/C ratio of 1.58.